Alcoholic and Nonalcoholic Fatty Liver Disease and Liver-Related Mortality: A Cohort Study. (April 2019) - Chang, Yoosoo; Cho, Yong Kyun; Cho, Juhee; Jung, Hyun-Suk; Yun, Kyung Eun; Ahn, Jiin; Sohn, Chong Il; Shin, Hocheol; Ryu, Seungho
Abstract : OBJECTIVES: We compared liver-related mortality by fibrosis severity between 2 types of fatty liver disease (FLD), nonalcoholic FLD (NAFLD) and alcoholic FLD (AFLD), in a large cohort of nonobese and obese individuals. METHODS: A cohort study was performed with 437, 828 Korean adults who were followed up for up to 14 years. Steatosis was diagnosed based on ultrasonography; fibrosis severity was determined by the fibrosis 4 (FIB-4) score. Vital status and liver-related deaths were ascertained through linkage to national death records. RESULTS: The prevalence of NAFLD and AFLD was 20.9% and 4.0%, respectively. During 3, 145, 541.1 person-years of follow-up, 109 liver-related deaths were identified (incidence rate of 3.5 per 10 5 person-years). When changes in fatty liver status, FIB-4 scores, and confounders during follow-up were updated as time-varying covariates, compared with the reference (absence of both excessive alcohol use and FLD), the multivariable-adjusted hazard ratios with 95% confidence intervals for liver-related mortality among those with low, intermediate, and high FIB-4 scores were 0.43 (0.19–0.94), 2.74 (1.23–6.06), and 84.66 (39.05–183.54), respectively, among patients with NAFLD, whereas among patients with AFLD, the corresponding hazard ratios (95% confidence intervals) were 0.67 (0.20–2.25), 5.44 (2.19–13.49), and 59.73 (27.99–127.46), respectively. The associations were more evident in nonobese individuals than in obese individuals ( P for interaction = 0.004). DISCUSSION: In this large cohort of young and middle-aged individuals, NAFLD and AFLD with intermediate to high fibrosis scores were associated with an increased risk of liver-related mortality in a dose-dependent manner, especially among nonobese individuals.